Sikap petani terhadap adopsi inovasi sistem tanam jajar legowo - Simatupang, Donny Ivan Samuel; Pakpahan, H.T.; Nazara, D.C.B. (Jurnal Agrotek Ummat, 2022)
The jajar legowo planting system needs to be implemented in all regencies/cities in North Sumatra, because this planting system is an attempt to optimized agricultural yields. This study purposes were: 1) determined the farmers’ attitude to implement the jajar legowo system; 2) determined the factors that influence the implementation of jajar legowo system at the research site; and 3) determined how farmers implemented the jajar legowo planting system at the research site. The method used to determine the research location applies purposive sampling. The method of determining the sample used is "Stratified Random Sampling" based on the area of land cultivated by farmers. The analytical method to determine the factors that influenced the farmers’ attitude to implement the jajar legowo system used a Liker scale, while the analytical method determined the factors that influenced the implementation of the jajar legowo system used multiple linear regression. The research results can be concluded that 1) the farmers’ positive attitudes towards the jajar legowo system were 16 people (53.33%), and negative attitudes were 14 people (46.67%). The positive attitude was shown by the farmers being satisfied with the jajar legowo system. 2) Simultaneously, the factors of physical capital, social capital, and human capital have not real influence on farmers’ attitudes in implementing the jajar legowo system. 3) Farmers who implement the jajar legowo system are 21 farmers (70%) and those who do not implement it are 9 farmers (30%).